Development of a core data set for pelvic floor disorder patients registry. Issue 1 (16th September 2020) - Abdi Reyhan, Masoumeh; Damanabi, Shahla; Kalankesh, Leila R.; Hajebrahimi, Sakineh
Abstract: Objectives: Pelvic floor disorders (PFDs) are important public health concerns due to their increasing prevalence. Hence, there is an increasing need for developing systematically collected quality data to assist appropriate clinical decision‐making. This study aimed to develop a core data set for patients with PFDs based on the PFDs registry. Methods: A descriptive cross‐sectional study was conducted in 2019. Data were retrieved from electronic databases including PubMed, Embase and Google scholar. Available documents and data systems in clinical centers were also assessed. The Delphi technique was applied to reach a consensus about the data elements using a questionnaire. A panel of experts evaluated the content validity of the questionnaire. Results: We developed a dataset for PFDs that included two classes of data (65 data items) identified from the related literature. In the Delphi survey, 74 data elements were determined by the experts and final data were divided into two demographic and clinical categories that included 12 and 62 data elements, respectively. Conclusions: This dataset has the potential for standardizing the data by providing accurate, consistent, complete and uniform data elements. Furthermore, it can provide valuable research facilities for clinicians and researchers in the healthcare system resulting in improvement of the quality of care and containment of costs.